The performance analysis of PID controller for rehabilitation by using dynamic model - Roy, Rupal; Rashid, Muhammad Mahbubur; Islam, Maidul; Nayen, Julkar; Paul, Anik; Zainul Azlan, Norsinnira (The Mattingley Publishing Co., Inc., 2020)
This work investigates the performance of 2DOF (degree of freedom) PID (Proportional Integral Derivative) controller on upper limb rehabilitation robots in order to control elbow flexion and extension with a range of 0 to 115 degree. As simple PID is not able to ensure always promising performance like 0% overshoot with fast rise time and settling time while such a performance from the controller is inevitable for patient’s safety and convenience, PID has been modified and renamed as 2DOF PID controller. A new algorithm has been adopted to design 2DOF PID controller. This work has been carried out in simulation in order to measure the initial performance of the system before moving to hardware implementation. MATLAB & Simulink environment has been considered for simulation work. Sinusoidal trajectory is considered to evaluate the performance of the controller. However, the controller performance is satisfactory as both rising time and settling time have been found less than 1 second and overshoot and undershoot have exhibited zero percent.